ANALISIS PENGARUH PAD DAN BELANJA PEMBANGUNAN TERHADAP KINERJA KEUANGAN DAERAH DI KABUPATEN dan KOTA se-JAWA TIMUR - YASIN, MUHAMMAD; KASINO, KASINO (JEB17 : Jurnal Ekonomi dan Bisnis, 2018)
ABSTRACTEconomic growth is the process of continually changing a country's economic condition towards a better condition for a certain period. Economic growth can also be interpreted as a process of increasing the production capacity of an economy that is realized in the form of an increase in national income. Free variable PAD (X1) Measured using: (1) Tax, (2) Non-tax, Development expenditure (X2) Measured using: (1) Development, (2) Growth. Independent variables Regional financial performance is measured using: (1) efficiency ratio, (2) effectiveness ratio, (3) independence ratio, (4) activity ratio. economic growth with this means that if the regional income will cause an increase in the achievement of economic growth. which is very flexible in terms of its utilization, causing regions to be more flexible in planning budget allocations for development activities in accordance with their economic agendas which include building basic facilities and infrastructure that play a role in supporting optimal economic growthÂ Keyword : PAD, Belanja Pembangunan, Kinerja Keuangan,Â